Determinant of bad practice habit among beginner brass player / Hafizan Shaharuddin - Shaharuddin, Hafizan (2019)
Practice for brass player is very important in order to achieve greater result in playing their instrument. Beginner brass player tend to develop bad habit of practicing. It is because the knowledge of beginner player is limited compared to player that have greater experience in playing. From this study, the researcher tries to depict what the professional player do in order to improve their practice session. By knowing what the professional player did, the researcher can provide a recommendation for the beginner to have an idea on how to start their practice effectively. This research also investigates the techniques the professional players used in their regular practice so that it can also be the regular practices for the beginner brass player.